PEMUDA (PENGE MBANGAN MITRA UMKM DAERAH LUNANG DUA ) STRATEGI PENGUATAN BRANDING PRODUK - Yola Yolanda; Gesang Pujaseno; Veline Patricia Damanik; Azfar Hadi Rama Yasmen; Rani Sofya (Universitas Negeri Padang, 2019)
Micro Small and Medium Enterprises (MSME) are one of the sectors supporting the economy of the people in the Lunang II area of Pesisir Selatan Regency. MSME in the Lunang Dua area still have several problems to compete or survive in the Industry 4.0 era. The first problem were they do not have a brand or image that is easy to recognize by potential customers. The second problem were they don’t have attractive product packaging. The third problem were they still limited marketing area. Through the activities of the team Technology Student Creativity Program (PKM T), the team carried out educational activities to partners about the importance of the brand for the product. In an effort to improve the competitiveness of MSME, especially in the Lunang Dua area, it was carried out by branding the names of MSME partners to become the Barokah MSME which later became their own identity for local, national and international marketing. To improve the quality of product packaging, the partners of the PKMT team helped design attractive packaging and can compete with competitors' products and match the characteristics of partner products. The PKM T team also built and developed a website in the form of an online shop as a means of online sales so that it expands the market from partners, namely Barokah MSME. The team also helped make Barokah's MSME social media in the form of instagram to increase sales of partner products. To increase the usefulness of this online market for partners, the team provides web and UMKM Instagram training to partners. The Barokah MSME brand and the improvement of product packaging quality and the existence of an online shop that can be operated easily by partners are expected to expand the marketing area of partner products and increase sales volume and improve the welfare of partners.